Regionalisme dan Dampaknya dalam Pemilihan Presiden di Korea Selatan - ANNISSA, JEANIE (Politeia: Jurnal Ilmu Politik, 2011)
The issue of regionalism became one of the important issues during 1992. The main issue is the economic improvement. Industry in South Korea is located in the Kyongsang are experiencing rapid economic improvement. Contrast with Cholla as an agricultural region. Social inequali-ties also become an important issue raised during the Presidential Election and elites use the local history to control society. This paper discusses the regionalism and the impact in presi-dential election in South Korea. The paper indicates the regionalism under the authoritarian military system and how the regionalism can create the political cleavage in the regional and appear to contribute in the election party. Creating the Regionalism issues influence the corre-lation between economic growth and political growth. In this point, economic growth influence by democratic transition without sentiment regional. Good levels of literacy in South Korea contribute to the formation of the social system with a better political culture.Keywords: Regionalism, election, regime.